2021
DOI: 10.1186/s12889-021-11687-8
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness during COVID-19: challenges, responses, and lessons learned from homeless service providers in Tippecanoe County, Indiana

Abstract: Background The COVID-19 pandemic laid bare some of the United States’ most devastating health and social inequities faced by people experiencing homelessness. Homeless populations experience disproportionate rates of underlying health conditions, stigma and marginalization that often disenfranchise them from health and social services, and living conditions that potentiate the risk of COVID-19 transmission and adverse outcomes. Methods Guided by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 18 publications
5
74
1
Order By: Relevance
“…Fear or perceived threat of COVID-19 among PEH was discussed by ten studies [ 12 , 13 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Fear varied across studies; in Los Angeles, 65% of tenants of permanent supportive housing surveyed by Henwood et al [ 85 ] in March 2020 regarded COVID-19 as a serious risk to their health, while 33% of those surveyed in Los Angeles by Kuhn et al [ 87 ] from December 2020 to February 2021 perceived it as a high threat.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fear or perceived threat of COVID-19 among PEH was discussed by ten studies [ 12 , 13 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Fear varied across studies; in Los Angeles, 65% of tenants of permanent supportive housing surveyed by Henwood et al [ 85 ] in March 2020 regarded COVID-19 as a serious risk to their health, while 33% of those surveyed in Los Angeles by Kuhn et al [ 87 ] from December 2020 to February 2021 perceived it as a high threat.…”
Section: Resultsmentioning
confidence: 99%
“…A third study in Los Angeles carried out from April to June 2020 reported that 53% of young PEH (18–25 years old) were not at all worried about COVID-19, and 15% were very or extremely worried [ 88 ]. One study by Rodriguez et al [ 12 ] reported that PEH in Tippecanoe County, Indiana had an overall low risk perception of COVID-19, while authors of a study in France found that PEH felt that the virus was indeed a threat but was not a major concern compared to the other risks they regularly faced [ 13 ]. Using data from Hamburg, Hajek et al [ 89 ] found that increased fear of COVID-19 among PEH was associated with younger age, absence of chronic alcohol consumption, increased perceived own risk of contracting the virus one day, and a higher agreement that a diagnosis of COVID-19 would ruin their life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations